2004
DOI: 10.1099/mic.0.27426-0
|View full text |Cite
|
Sign up to set email alerts
|

The pmrF polymyxin-resistance operon of Yersinia pseudotuberculosis is upregulated by the PhoP-PhoQ two-component system but not by PmrA-PmrB, and is not required for virulence

Abstract: The pmrF polymyxin-resistance operon of Yersinia pseudotuberculosis is upregulated by the PhoP-PhoQ two-component system but not by PmrA-PmrB, and is not required for virulence The Yersinia pseudotuberculosis chromosome contains a seven-gene polycistronic unit (the pmrF operon) whose products share extensive homologies with their pmrF counterparts in Salmonella enterica serovar Typhimurium (S. typhimurium), another Gram-negative bacterial enteropathogen. This gene cluster is essential for addition of 4-aminoar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 50 publications
3
45
0
3
Order By: Relevance
“…We had previously observed that when exponentially growing Y. pseudotuberculosis IP32777 was inoculated into growth medium supplemented with the iron chelators desferral or 2,2-dipyridyl, the resistance of the bacterium to polymyxin B increased about 20-fold (Marceau et al, 2004). In the present study, we assessed whether this phenotype could also be observed in the closely related enteropathogenic species Y. enterocolitica (Bottone, 1997) under iron availability limitation conditions.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…We had previously observed that when exponentially growing Y. pseudotuberculosis IP32777 was inoculated into growth medium supplemented with the iron chelators desferral or 2,2-dipyridyl, the resistance of the bacterium to polymyxin B increased about 20-fold (Marceau et al, 2004). In the present study, we assessed whether this phenotype could also be observed in the closely related enteropathogenic species Y. enterocolitica (Bottone, 1997) under iron availability limitation conditions.…”
Section: Resultsmentioning
confidence: 80%
“…Conversely, expression of this gene was diminished by nearly threefold in Y. pseudotuberculosis after inactivation of YPTB0333. Although this reduction was not statistically significant [most likely because pmrF transcription has been shown to be regulated by other means, such as the two-component system regulator PhoP (Marceau et al, 2004)], YPTB0333…”
Section: Yptb0333 Binds To the Promoter Region Of The Pmrf Operonmentioning
confidence: 99%
See 1 more Smart Citation
“…TCS PhoP-PhoQ system of Salmonella and Yersinia pestis is responsible for the virulence within animal host cells [13][14][15]. PhoPPhoQ of X. oryzae pv.…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella species are facultative intracellular pathogens that can infect a wide variety of animals causing different diseases [12]. A phoP mutant of the etiologic agent of bubonic plagues Yersinia pestis [13,14], reduced the abilities to survival within macrophages, and increased sensitivity to low pH, oxidative stress, and high osmolarity [15]. A phoP deficient of Shigella is hypersensitive to killing by neutrophils [16].…”
Section: Introductionmentioning
confidence: 99%